Harta bersama barang perhiasan (Analisis Putusan Hakim Nomor 57/Pdt.G/2004/PA. Watampone) - Jasmani, Jasmani (An - Nisa`, 2012)
Abstract: Community property is one marriage asset type that ruled deep legislation at Indonesian. The importance for appearance community property while happens marriage dispersal, well by separate and also effect death scene. Female ornamental goods is marriage asset that becomes difference opinion judge, so problem appearance marriage happens community property or not. Concerning with that things, this writing explains one analysis academic.